2011
DOI: 10.1158/1535-7163.mct-10-1053
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibition of the Functional Interaction between Integrin α6β4 and the Epidermal Growth Factor Receptor

Abstract: The functional interaction between integrin a6b4 and growth factor receptors has been implicated in key signaling pathways important for cancer cell function. However, few attempts have been made to selectively target this interaction for therapeutic intervention. Previous studies showed that curcumin, a yellow pigment isolated from turmeric, inhibits integrin a6b4 signaling important for breast carcinoma cell motility and invasion, but the mechanism is not currently known. To address this issue, we tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…uPA levels were also decreased in curcumin-treated cells, in which inhibition of NF-kB activity was identified as the chief culprit . Similarly, inhibition of tumor metastasis by curcumin has been frequently observed and attributed to the reduction in MMP-2, MMP-9, uPA, and aquaporin 3 protein levels Weissenberger et al, 2010;Wong et al, 2010;Soung and Chung, 2011). Although the mechanism is relatively elusive, aquaporins play a role in tumor growth and metastasis (Nico and Ribatti, 2010), during which MMPs are upregulated via the PI3K-Akt pathway to facilitate these processes.…”
Section: Ink4amentioning
confidence: 99%
“…uPA levels were also decreased in curcumin-treated cells, in which inhibition of NF-kB activity was identified as the chief culprit . Similarly, inhibition of tumor metastasis by curcumin has been frequently observed and attributed to the reduction in MMP-2, MMP-9, uPA, and aquaporin 3 protein levels Weissenberger et al, 2010;Wong et al, 2010;Soung and Chung, 2011). Although the mechanism is relatively elusive, aquaporins play a role in tumor growth and metastasis (Nico and Ribatti, 2010), during which MMPs are upregulated via the PI3K-Akt pathway to facilitate these processes.…”
Section: Ink4amentioning
confidence: 99%
“…Notably, cooperative signaling has been identified between integrin α6β4 and multiple members of the EGFR family. EGFR and integrin α6β4 have also been shown to co-localize at the leading edge of carcinoma cells subjected to EGF stimulation, and their interaction was inhibited by curcumin, a compound present in turmeric (48). Integrin α6β4 has also been shown to associate with ErbB-2 in multiple breast carcinoma cell lines (30, 49), though reports are conflicting as to whether integrin α6β4 expression correlates with ErbB-2 protein overexpression in patient-derived carcinoma tissues (5053).…”
Section: Integrin α6β4 Signaling In Malignant Cellsmentioning
confidence: 99%
“…It was reported that S-acylation of metastasis-associated proteins KAT1/CD82, CD9, and CD151 is essential for their function of suppressing metastasis or inhibiting tumor cell adhesion and migration (Zhou et al, 2004; Hemler, 2014; Termini et al, 2014). Integrin β4 (ITGβ4) can interact with growth factor receptors and enhance invasive potential of cancer cells (Soung and Chung, 2011). This is helped by the S-acylation of ITGβ4 which is required for its lipid raft localization in the membrane and signaling activity.…”
Section: S-acylationmentioning
confidence: 99%